On Verhoeff’s Otostigmus subgenus Malaccopleurus, the nudus group of Otostigmus subgenus Otostigmus Porat, 1876, and Digitipes Attems, 1930, with a description of the foetus stadium larva in O. sulcipes Verhoeff, 1937, (Chilopoda: Scolopendromorpha: Scolopendridae) - Lewis, John G. E. (Zootaxa, 2015)
The species of Verhoeff’s Southeast Asian subgenus Malaccopleurus (an unavailable name) are here assigned to subgenus Otostigmus. His Otostigmus (M.) trisulcatus Verhoeff, 1937 is a junior subjective synonym of O. (M.) sulcipes Verhoeff, 1937. The foetus stadium of O. sulcipes is described. Otostigmus (M.) sutteri Würmli, 1972, is also assigned to the subgenus Otostigmus and may be conspecific with O. geophilinus Haase, 1887, the specimens of which show some variation. The specimen from Teinzo, Myanmar with labels O. politus Karsch, 1881, and O. geophilinus is of uncertain identity. Otostigmus sulcipes closely resembles O. nudus Pocock, 1890, and O. taeniatus Pocock, 1896, of Lewis’s (2010) nudus group. Otostigmus lawrencei Dobroruka, 1968, resembles a Cormocephalus species and is of uncertain identity. The genus Digitipes is characterised by the process on the femur of the ultimate legs in males. Three African species have been recognised. The males of Digitipes verdascens Attems, 1930, D. reichardti (Kraepelin, 1903) are known but D. krausi Dobroruka, 1968, lacks the femoral process and was described as a female. In these three species, only the tergite of the ultimate leg-bearing segment is marginate but in other characters D. krausi resembles Otostigmus species and is assigned to Otostigmus as O. krausi (Dobroruka, 1968) comb. nov. The Indian Digitipes periyarensis Joshi & Edgecombe, 2013, which differs markedly from other Digitipes species is a junior subjective synonym of Otostigmus nudus. It is possible that future molecular studies may show that some species currently assigned to Otostigmus are, in fact, Digitipes.